Researching and Thematic Tendencies on Colombia’s Faculties of Education: a View on the Journals (2016)
It is sought with this article to make an inquiry on the concept of research adopted by the departments of education in some Colombian universities. In order to achieve so, it is proposed an online-digital literary review on some of the most important journal indexes in where education and pedagogy have become in the main characters. Based on some statistics, national and international rankings as references, the paper does not pretend to inquire into what research is, that is to say, the text is not in the pursuit of defining the concept itself; instead of that, it aims to do an assessment about the researching tendencies that from the academy —especially from education departments— allow to understand how is this (the research) being thought.